Jordan - Poverty Assessment (Vol. 2 of 2) : Main Report - World Bank (Washington, DC, 2013)
This report assesses poverty in Jordan in 2002-03, and examines the changes that have occurred since 1997 as a result of economic growth and the income distribution policies of the Government of Jordan. The study concludes that poverty declined in Jordan in that time period, no matter which poverty line one chooses to use, and was made possible with an equally remarkable growth in per capita private consumption, in which the poor participated, at about 3.5 percent a year. The fast rise in private consumption appears to be due to a recovery in consumption trends that is mainly policy driven. The report, however, identifies some concerns about the sustainability of poverty reduction, and recommends that long-term policy focus more on regional imbalances in development; improve access of the poor in education, health, and jobs; plug the leakage in government transfer programs; and institute poverty monitoring systems for timely remedial action.